1978
DOI: 10.1172/jci109229
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the tubulo-glomerular feedback system in the rat. The mechanism of reduction in filtration rate with benzolamide.

Abstract: The specific mechanism whereby superficial nephron glomerular filtration rate (sngfr) is reduced after the administration of benzolamide, a carbonic anhydrase inhibitor with a primary inhibitory effect in the proximal tubule, have been examined by measuring pertinent pressures, flows, and glomerular permeabilities in the hydropenic Munich-Wistar rat, a strain with surface glomeruli. Because benzolamide decreases absolute proximal reabsorptive rate, the rate of delivery of tubular fluid to the distal nephron sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 28 publications
2
40
0
Order By: Relevance
“…These authors have shown earlier that an acute inhibition of proximal NaHCO 3 absorption by the carbonic anhydrase inhibitor benzolamide causes an increase in salt delivery to the macula densa, accompanied by the predicted TGF-mediated reduction in filtration rate (16). Their new results demonstrate that repeated administration of benzolamide over 24 hours, which results in prolonged hyperperfusion of the macula densa, induces a rightward and upward shift of the TGF curve ( Figure 2).…”
mentioning
confidence: 78%
“…These authors have shown earlier that an acute inhibition of proximal NaHCO 3 absorption by the carbonic anhydrase inhibitor benzolamide causes an increase in salt delivery to the macula densa, accompanied by the predicted TGF-mediated reduction in filtration rate (16). Their new results demonstrate that repeated administration of benzolamide over 24 hours, which results in prolonged hyperperfusion of the macula densa, induces a rightward and upward shift of the TGF curve ( Figure 2).…”
mentioning
confidence: 78%
“…Experimental studies in animals have shown that carbonic anhydrase inhibitors reduce proximal tubular reabsorption of water and sodium [4,5,[20][21][22]. Acute administration of acetazolamide has been reported to increase lithium clearance and reduce proximal tubular reabsorption of sodium and water in man [16].…”
Section: Discussionmentioning
confidence: 99%
“…Acute administration of acetazolamide has been reported to increase lithium clearance and reduce proximal tubular reabsorption of sodium and water in man [16]. The acute decline in GFR is probably mediated by the tubulo-glomerular feedback mechanism [4,5,20,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BNZ acutely reduces proximal reabsorption by approximately 50%, thereby increasing fluid entry to the loop of Henle, with subsequent activation of TGF. Administered acutely, BNZ causes a TGF-mediated reduction in GFR (3). (In pilot studies performed in awake rats, single intraperitoneal doses of BNZ exerted a diuretic effect that lasted less than 6 hours.).…”
Section: Methodsmentioning
confidence: 99%